2016
DOI: 10.3325/cmj.2016.57.465
|View full text |Cite
|
Sign up to set email alerts
|

Remineralizing amorphous calcium phosphate based composite resins: the influence of inert fillers on monomer conversion, polymerization shrinkage, and microhardness

Abstract: AimTo determine if the addition of inert fillers to a bioactive dental restorative composite material affects its degree of conversion (DC), polymerization shrinkage (PS), and microhardness (HV).MethodsThree amorphous calcium phosphate (ACP)-based composite resins: without added fillers (0-ACP), with 10% of barium-glass fillers (Ba-ACP), and with 10% of silica fillers (Si-ACP), as well as commercial control (Ceram•X, Dentsply DeTrey) were tested in laboratory conditions. The amount of ACP (40%) and the composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Among these nano-amorphous calcium phosphate (NACP) had been used in 15 studies 19,[21][22][23][24][25][26][27][28][29][30][31]57,58,62) , and the rest were based on micro-ACP. Moreover, zirconia 8,[32][33][34][35][36][37][38][39][40] and silica 8,39,41) had been hybridized with ACP to improve the mechanical and biological properties Nano-silver particles 27,57) and HA powder 42) were also mixed with ACP to analyze the antibacterial and mechanical properties, respectively. In vivo studies were found related to human 16,17) and rat models 18,19) .…”
Section: Acpmentioning
confidence: 99%
“…Among these nano-amorphous calcium phosphate (NACP) had been used in 15 studies 19,[21][22][23][24][25][26][27][28][29][30][31]57,58,62) , and the rest were based on micro-ACP. Moreover, zirconia 8,[32][33][34][35][36][37][38][39][40] and silica 8,39,41) had been hybridized with ACP to improve the mechanical and biological properties Nano-silver particles 27,57) and HA powder 42) were also mixed with ACP to analyze the antibacterial and mechanical properties, respectively. In vivo studies were found related to human 16,17) and rat models 18,19) .…”
Section: Acpmentioning
confidence: 99%
“…The issue of secondary caries has enticed our research group to develop remineralizing bioactive materials with the addition of amorphous calcium phosphate (ACP) [ 3 , 4 , 5 , 6 ] and 45S5 bioactive glass (BG) fillers [ 7 , 8 , 9 , 10 , 11 ]. The supersaturated calcium and phosphate ion concentrations released by ACP resin composites have been shown to induce hydroxyapatite formation and remineralization [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Silica nanofillers (SiO 2 ) have been shown to enhance apatite formation on the surface of both ACP and BG composites [ 4 ]. However, the amorphous structure and solubility of ACP fail to provide strong mechanical properties of resin composites [ 3 , 4 , 5 ]. Similar behavior was demonstrated by BG resin composites, whose mechanical properties and degree of conversion (DC) deteriorated in a dose-dependent manner with the increase in BG ratio [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…119,120 Silanized inert fillers in the original ACP formulation Circumvented polymerization shrinkage, which is an undesirable consequence of high conversion rates. 38 Whiskers with nDCPA Fast release of Ca and PO 4 ions, due to the large surface area of the nDCPA particles, 119 which has been shown to re-precipitate and form hydroxyapatite inside tooth lesions outside the margins of the restoration. 121 Zirconia-silica clusters (0.…”
Section: Restorative Resin Compositesmentioning
confidence: 99%